Factors influencing the swelling behaviour of polymethyl vinyl ether-co-maleic acid hydrogels crosslinked by polyethylene glycol - Chandran, Rubhan; Mohd Tohit, Eusni Rahayu; Stanslas, Johnson; Tuan Mahmood, Tuan Mazlelaa; Salim, Norazlinaliza (Elsevier, 2022)
In past decades, polyethylene glycol (PEG) crosslinked polymethyl vinyl ether-co-maleic acid (PMVE/MA) hydrogel systems have been studied for various biomedical applications, mainly in the field of drug delivery. Nevertheless, successful delivery of clinically relevant dosage, especially high molecular weight drugs is still a major hindrance for this hydrogel system which delays its progress into clinical trials. Since the swelling property of this hydrogel plays a crucial role in its effectiveness as a drug delivery vehicle, we have investigated the influence of environmental factors such as pH, crosslinking temperature and swelling medium on their swelling pattern. Besides, we have also performed a comparison study on the effect of widely used foaming agents (NaHCO3 and Na2CO3) in the swelling kinetics and network properties of PEG crosslinked PMVE/MA hydrogels. The % swelling at 24 h for hydrogels with Na2CO3 was 3463%, significantly higher than hydrogels with NaHCO3 (1212%), suggesting the former as a better alternative for the delivery of macromolecular drugs. Besides, a slight increase in formulation pH and a decrease in the crosslinking temperature by 10 °C resulted in a significantly higher Seq% for the hydrogels. We also reported that the hydrogel exhibit significantly enhanced swelling characteristics in neutral and alkaline conditions compared to the acidic medium. These findings suggest that environmental factors such as pH and temperature and chemical factors such as the type of foaming agents strongly affect the swelling and network characteristics of PEG crosslinked PMVE/MA hydrogels. Therefore, these factors can be customised accordingly to regulate the release of therapeutics from PMVE/MA hydrogels as well as widen its application in biomedicine.